Water quality of the Bacauan River and Diday Creek during the rainy period - Pineda, Shienna Mae Maghuyop (2005.)
Water samples from Bacauan River (Sites A, B, and D) and Diday Creek (Site C) were subjected to physico-chemical analyses (temperature, turbidity, color, pH, acidity, alkalinity, hardness, nitrate, solids, total dissolved solids) and microbiological analyses (TPC and MPN for total and fecal coliforms).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Water quality; Bacauan River; Diday Creek